Pseudobagrus fui Miao, a valid bagrid species from the Yangtze River drainage, South China (Teleostei: Bagridae) - Cheng, Jian-Li; López, J. Andrés; Zhang, E (Zootaxa, 2009)
Pseudobagrus fui Miao is a valid bagrid species that can be separated from all its congeners in having 27–33 anal-fin rays. Among the species of Pseudobagrus, it forms part of a group of approximately 20 species putatively characterized by having a smooth anterior margin of the pectoral-fin spine and short maxillary barbels not extending to the base of the pectoral-fin spine. Pseudobagrus fui, together with P. nitidus and P. vachelli, can be differentiated from all other forktailed species of this group by having no fewer than 20 branched anal-fin rays, the posterior end of the anal-fin base posterior to the vertical through the posterior end of the adipose-fin base, and anal-fin base longer than the adipose-fin base. It further differs from P. nitidus in having a gas bladder without beaded lateral and posterior margins, and from P. vachelli in having short maxillary barbels not extending to the base of the pectoral-fin spine. Pseudobagrus fui is currently known from the main stream of the upper Yangtze River and its tributaries, the Min River, Jialing River, Tuo River, Wu River and Chishui River in Sichuan Province, Guizhou Province, and the Chongqing City. The identity and nomenclature of Pseudobagrus nitidus is also discussed.